Research on eight machine learning algorithms applicability on different characteristics data sets in medical classification tasks - Zhang, Yiyan; Li, Qin; Xin, Yi (Frontiers in Computational Neuroscience, 2024)
With the vigorous development of data mining field, more and more algorithms have been proposed or improved. How to quickly select a data mining algorithm that is suitable for data sets in medical field is a challenge for some medical workers. The purpose of this paper is to study the comparative characteristics of the general medical data set and the general data sets in other fields, and find the applicability rules of the data mining algorithm suitable for the characteristics of the current research data set. Most medical research can be transformed into classification problems, but there is no prior knowledge on how to quickly select the suitable algorithm for current research among numerous data mining algorithms. The study quantified characteristics of the research data set with 26 indicators, including simple indicators, statistical indicators and information theory indicators. Eight machine learning algorithms with high maturity, low user involvement and strong family representation were selected as the base algorithms. The algorithm performances were evaluated by three aspects: prediction accuracy, running speed and memory consumption. By constructing decision tree and stepwise regression model to learn the above metadata, the algorithm applicability knowledge of medical data set is obtained. Through cross-verification, the accuracy of all the algorithm applicability prediction models is above 75%., which proves the validity and feasibility of the applicability knowledge.